2007
DOI: 10.1007/s00296-007-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

P wave dispersion in patients with rheumatoid arthritis: its relation with clinical and echocardiographic parameters

Abstract: P wave dispersion (PWD) is a sign for the prediction of atrial fibrillation (AF). The aim of this study was to assess P wave dispersion and its relation with clinical and echocardiographic parameters in patients with rheumatoid arthritis (RA). Thirty RA patients (mean age 49 +/- 10 years) and 27 healthy controls (mean age 47 +/- 8 years) were included in the study. We performed electrocardiography and Doppler echocardiography on patients and controls. Maximum and minimum P wave duration were obtained from elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
2
17
0
2
Order By: Relevance
“…Higher P wave dispersion was associated with LVDD in previous studies 18, 20, 35. After the multivariate analysis, our study consistently demonstrated that increased PWDC was significantly associated with increased E/Ea and LVDD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Higher P wave dispersion was associated with LVDD in previous studies 18, 20, 35. After the multivariate analysis, our study consistently demonstrated that increased PWDC was significantly associated with increased E/Ea and LVDD.…”
Section: Discussionsupporting
confidence: 86%
“…The P wave dispersion measured by 12-lead ECG was found to be associated with the occurrence of atrial fibrillation 21, 28, 32-34, left atrial enlargement and increased LAV index 16, 35. Higher P wave dispersion was associated with LVDD in previous studies 18, 20, 35.…”
Section: Discussionmentioning
confidence: 65%
“…Prolonged electromechanical delays and impaired left atrial mechanical functions were observed in RA patients and correlated with CRP level 11. P‐wave dispersion was found to be increased in RA and correlated with CRP and disease duration 12. P‐wave dispersion is considered as an electrocardiographic marker of inhomogeneous and discontinuous propagation of sinus impulses in the atrial myocardium, representing a sensitive and specific clinical predictor of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis P-wave duration and PWD was found to be higher in rheumatoid arthritis patients than healthy control subjects [42].…”
Section: Normal Limit Values Of P-wave Dispersion (Pwd)mentioning
confidence: 99%